Ultraviolet barrier film as well as preparation method and application thereof

By using ultraviolet barrier film composed of polyvinyl alcohol, sodium carboxymethylcellulose, carbon quantum dots and horseshoe starch, the problem of degradation of food packaging materials in UV irradiation and insufficient moisture barrier performance during UV irradiation is solved, and efficient ultraviolet and moisture are achieved Blocking, suitable for industrial applications in the field of food packaging.

CN119119660AActive Publication Date: 2024-12-13SOUTH CHINA UNIV OF TECH +1

Patent Information

Application Number
CN202411085138.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2024-12-13
Estimated Expiration
2044-08-08

AI Technical Summary

Technical Problem

Existing food packaging materials are prone to degradation under ultraviolet irradiation, resulting in pollution and decomposition of nutrients, and insufficient moisture barrier performance, which cannot fully meet the practical application requirements.

Method used

An ultraviolet barrier film composed of polyvinyl alcohol, sodium carboxymethylcellulose, carbon quantum dots and horseshoe starch was prepared by specific dissolution, stirring, gelatinization and drying processes to form a thin film with excellent ultraviolet and moisture barrier properties.

Benefits of technology

It has achieved packaging materials with excellent ultraviolet barrier properties, good moisture barrier properties, high mechanical strength, high transparency, green and environmentally friendly, and degradable packaging materials. It is suitable for the food packaging field, and has simple preparation methods and low production costs, which are suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119660A_ABST
    Figure CN119119660A_ABST
Patent Text Reader

Abstract

The invention discloses an ultraviolet barrier film as well as a preparation method and application thereof. The ultraviolet barrier film is prepared from the following raw materials in percentage by weight: 20-40% of polyvinyl alcohol; 20%-30% of sodium carboxymethyl cellulose; 5%-10% of carbon quantum dots; and 30%-45% of water chestnut starch. The preparation method of the ultraviolet barrier film comprises the following steps: 1) preparing a polyvinyl alcohol solution, a sodium carboxymethyl cellulose solution, a carbon quantum dot dispersion liquid and a water chestnut starch solution; 2) preparing gelatinized mixed slurry; and 3) carrying out film casting on the gelatinized mixed slurry, and drying to obtain the ultraviolet barrier film. The ultraviolet barrier film has the advantages of being excellent in ultraviolet barrier performance, good in moisture barrier performance, high in mechanical strength, high in transparency, environmentally friendly, degradable and the like, can be used as a packaging material, and is simple in preparation method, low in production cost and suitable for large-scale industrial production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of packaging materials, and in particular to an ultraviolet blocking film and a preparation method and application thereof. Background Art

[0002] Food packaging is an important part of food commodities, which can effectively prevent food from being damaged by biological, chemical, and physical external factors. However, existing food packaging is prone to degradation of packaging materials when exposed to ultraviolet rays from sunlight. The substances produced by degradation will directly contaminate food and eventually endanger people's health. In addition, ultraviolet radiation will cause many nutrients in food to decompose, which is not conducive to the storage and transportation of food. In addition, the existing food packaging has poor barrier properties against moisture, and moisture can also cause food contamination and damage. In summary, existing packaging materials cannot fully meet the requirements of practical applications.

[0003] Therefore, it is of great significance to develop a food packaging material with excellent UV barrier properties, good moisture barrier properties, and green environmental protection. Summary of the invention

[0004] The purpose of the present invention is to provide an ultraviolet blocking film and a preparation method and application thereof.

[0005] The technical solution adopted by the present invention is:

[0006] A UV blocking film, which is made of the following raw materials in percentage by weight:

[0007] Polyvinyl alcohol: 20% to 40%;

[0008] Sodium carboxymethyl cellulose: 20%-30%;

[0009] Carbon quantum dots: 5% to 10%;

[0010] Horse hoof starch: 30%~45%.

[0011] Preferably, the number average molecular weight of the polyvinyl alcohol is 250,000-300,000.

[0012] Preferably, the particle size of the carbon quantum dots is 5 nm to 10 nm.

[0013] Preferably, the carbon quantum dots are made from waste leather. Making waste leather into carbon quantum dots not only reduces environmental pollution caused by waste leather, but also realizes resource utilization of waste leather.

[0014] Further preferably, the carbon quantum dots are made by a preparation method comprising the following steps: removing chromium from waste leather, then adding it into water together with calcium oxide (CaO) for immersion to obtain a collagen extract, then subjecting the collagen extract to a microwave-assisted hydrothermal reaction, and then freeze-drying to obtain carbon quantum dots.

[0015] Preferably, the specific operation of the chromium removal treatment is as follows: immersing the waste leather in a sodium carbonate solution for soaking treatment, and then taking it out and rinsing it with water.

[0016] Preferably, the immersion treatment is carried out at a temperature of 70° C. to 90° C., and the treatment time is 20 h to 30 h.

[0017] Preferably, the weight ratio of the waste leather to calcium oxide is 1:0.1-0.4.

[0018] Preferably, the immersion treatment is carried out at a temperature of 50° C. to 70° C., and the treatment time is 3 h to 10 h.

[0019] Preferably, the microwave-assisted hydrothermal reaction is carried out under the conditions of a microwave power of 500W to 1000W and a temperature of 170°C to 210°C, and the reaction time is 40min to 90min.

[0020] Preferably, the particle size of the water chestnut starch is ≤50 μm.

[0021] Preferably, the surface density of the UV blocking film is 13 g / m 2 ~20g / m 2 .

[0022] A method for preparing the ultraviolet blocking film as described above comprises the following steps:

[0023] 1) adding water to dissolve / disperse polyvinyl alcohol, sodium carboxymethyl cellulose, carbon quantum dots and water chestnut starch respectively to prepare polyvinyl alcohol solution, sodium carboxymethyl cellulose solution, carbon quantum dot dispersion and water chestnut starch solution;

[0024] 2) mixing the polyvinyl alcohol solution, the sodium carboxymethyl cellulose solution, the carbon quantum dot dispersion and the water chestnut starch solution uniformly, and then heating to perform gelatinization reaction to obtain a gelatinized mixed slurry;

[0025] 3) Casting the gelatinized mixed slurry into a film, and then drying it to obtain a UV blocking film.

[0026] Preferably, the mass fraction of the polyvinyl alcohol solution in step 1) is 4% to 8%.

[0027] Preferably, the mass fraction of the sodium carboxymethyl cellulose solution in step 1) is 5% to 6%.

[0028] Preferably, the concentration of the carbon quantum dot dispersion in step 1) is 0.005 g / mL to 0.01 g / mL.

[0029] Preferably, the carbon quantum dots are dispersed in step 1) by stirring at a temperature of 25° C. to 35° C. and a stirring speed of 350 r / min to 450 r / min for 2 h to 3 h.

[0030] Preferably, the mass fraction of the water chestnut starch solution in step 1) is 8% to 10%.

[0031] Preferably, in step 1), the water chestnut starch is dissolved by ultrasonic dispersion, the ultrasonic power is 300W to 500W, the frequency is 15kHz to 25kHz, and the ultrasonic dispersion time is 10min to 15min.

[0032] Preferably, the gelatinization reaction in step 2) is carried out at a temperature of 80° C. to 85° C., and the reaction time is 10 min to 15 min.

[0033] Preferably, the drying in step 3) is carried out at a temperature of 30° C. to 40° C. and a relative humidity of 35% to 45%, and the drying time is 48 h to 72 h.

[0034] A food packaging material comprises the above-mentioned ultraviolet light blocking film.

[0035] The beneficial effects of the present invention are as follows: the ultraviolet blocking film of the present invention has the advantages of excellent ultraviolet blocking performance, good moisture blocking performance, high mechanical strength, high transparency, green environmental protection, and biodegradability, and can be used as a packaging material. The preparation method thereof is simple and the production cost is low, and the film is suitable for large-scale industrial production and application.

[0036] Specifically:

[0037] 1) The ultraviolet light blocking film of the present invention is added with carbon quantum dots, which are rich in functional groups such as amino, hydroxyl, and carboxyl groups, have the characteristics of low toxicity and good biocompatibility, and can convert ultraviolet rays passing through the film into fluorescence, thereby giving the film excellent ultraviolet light blocking performance (when the carbon quantum dots are directly irradiated by an external light source and excited, the energy level transition of photons will occur inside, thereby converting ultraviolet rays into fluorescence, and the fluorescence intensity of the carbon quantum dots can still remain stable after being irradiated by ultraviolet rays for a long time, and has strong light stability, and is suitable for preparing a biodegradable, sustainable, green and natural ultraviolet protection film);

[0038] 2) The ultraviolet blocking film of the present invention is added with natural polymer material water chestnut starch (also known as "water chestnut starch"), which has good water absorption and film-forming properties. Water chestnut starch molecules interact with water molecules through hydrogen bonds and then form a compact structure through gelatinization, thereby preventing further penetration of water. It can absorb moisture in the packaging space while keeping moisture from penetrating the film. This water-absorbing but impermeable property enables the film to effectively prevent the intrusion of external moisture while keeping the interior of the package dry, thereby extending the shelf life of the product in the package;

[0039] 3) The ultraviolet blocking film of the present invention has the advantages of excellent ultraviolet blocking performance, good moisture blocking performance, high mechanical strength, high transparency, green environmental protection, and biodegradability, and can be applied to the field of food packaging. The preparation method thereof is simple, safe, environmentally friendly, and has low production cost, and is suitable for large-scale industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The following are appearance diagrams of the ultraviolet blocking films in Examples 1 to 4 and the film in Comparative Example 1.

[0041] Figure 2 This is the appearance of the film in Comparative Example 2.

[0042] Figure 3 The graph is a test result of the ultraviolet blocking performance of the ultraviolet blocking films in Examples 1 to 4 and the film in Comparative Example 1.

[0043] Figure 4 This is a graph showing the water vapor transmission rate test results of the ultraviolet blocking films in Examples 1 to 4 and the film in Comparative Example 2.

[0044] Figure 5 The graph is a test result of moisture content and water solubility of the ultraviolet blocking films in Examples 1 to 4 and the film in Comparative Example 2. DETAILED DESCRIPTION

[0045] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0046] The preparation method of the carbon quantum dots in Examples 1 to 4 and Comparative Example 2 is as follows: 5 g of waste leather is chopped and immersed in a sodium carbonate solution with a pH value of 9.5 at 80°C for 24 h (to remove chromium), filtered, and the filtered solid is washed with deionized water, and then added to 120 g of deionized water, and 0.8 g of CaO is added, and stirred at 60°C for 5 h to extract to obtain a collagen extract, and then the collagen extract is transferred to a polytetrafluoroethylene-lined digestion tank, reacted at a microwave power of 800 W and a temperature of 190°C for 60 min, and then freeze-dried to obtain carbon quantum dots (particle size of 5 nm to 10 nm).

[0047] Embodiment 1:

[0048] A UV blocking film, the preparation method of which is as follows:

[0049] 1) Add 0.4 g of polyvinyl alcohol (number average molecular weight of 250,000) to 4.6 g of deionized water, stir for 3 h at 90° C. and 700 r / min to obtain a polyvinyl alcohol solution with a mass fraction of 8%; add 0.25 g of sodium carboxymethyl cellulose to 4.75 g of deionized water, stir for 2 h at 30° C. and 500 r / min to obtain a sodium carboxymethyl cellulose solution with a mass fraction of 5%. liquid; adding 0.05g of carbon quantum dots to 10g of deionized water, stirring for 2h at a temperature of 30°C and a stirrer speed of 400r / min to obtain a carbon quantum dot dispersion with a concentration of 0.005g / mL; adding 0.3g of water chestnut starch (particle size ≤50μm) to 3.35g of deionized water, and then ultrasonically dispersing for 10min at an ultrasonic power of 300W and an ultrasonic frequency of 20kHz to obtain a water chestnut starch solution with a mass fraction of 8%;

[0050] 2) mixing the polyvinyl alcohol solution, the sodium carboxymethyl cellulose solution, the carbon quantum dot dispersion and the water chestnut starch solution, stirring for 2 h at a temperature of 25 ° C and a stirrer speed of 400 r / min, then heating to 85 ° C and stirring at a constant temperature for 10 min to obtain a gelatinized mixed slurry;

[0051] 3) The gelatinized mixed slurry was cast into a film, and then placed in a constant temperature and humidity chamber at a temperature of 30°C and a relative humidity of 40% for 72 hours to obtain a UV blocking film (surface density of 13.01 g / m 2 ).

[0052] Embodiment 2:

[0053] A UV blocking film, the preparation method of which is as follows:

[0054] 1) Add 0.3 g of polyvinyl alcohol (number average molecular weight of 300,000) to 4.7 g of deionized water, stir for 3 h at 90° C. and 700 r / min to obtain a polyvinyl alcohol solution with a mass fraction of 6%; add 0.285 g of sodium carboxymethyl cellulose to 4.715 g of deionized water, stir for 3 h at 30° C. and 350 r / min to obtain sodium carboxymethyl cellulose with a mass fraction of 5.7% Solution; add 0.065g of carbon quantum dots to 13g of deionized water, stir for 3h at a temperature of 35°C and a stirrer speed of 400r / min to obtain a carbon quantum dot dispersion with a concentration of 0.005g / mL; add 0.35g of water chestnut starch (particle size ≤50μm) to 3.15g of deionized water, and then ultrasonically disperse for 10min at an ultrasonic power of 300W and an ultrasonic frequency of 20kHz to obtain a water chestnut starch solution with a mass fraction of 10%;

[0055] 2) mixing the polyvinyl alcohol solution, the sodium carboxymethyl cellulose solution, the carbon quantum dot dispersion and the water chestnut starch solution, stirring for 3 h at a temperature of 25 ° C and a stirrer speed of 350 r / min, then heating to 85 ° C and stirring at a constant temperature for 10 min to obtain a gelatinized mixed slurry;

[0056] 3) The gelatinized mixed slurry was cast into a film, and then placed in a constant temperature and humidity chamber at a temperature of 30°C and a relative humidity of 40% for 48 hours to obtain a UV blocking film (surface density of 14.05 g / m 2 ).

[0057] Embodiment 3:

[0058] A UV blocking film, the preparation method of which is as follows:

[0059] 1) 0.25 g of polyvinyl alcohol (number average molecular weight of 300000) was added to 3.92 g of deionized water, and stirred for 3 h at a temperature of 90 ° C and a stirring speed of 700 r / min to obtain a polyvinyl alcohol solution with a mass fraction of 6%; 0.265 g of sodium carboxymethyl cellulose was added to 4.735 g of deionized water, and stirred for 2 h at a temperature of 35 ° C and a stirring speed of 400 r / min to obtain sodium carboxymethyl cellulose with a mass fraction of 5.3%. Sodium cellulose solution; 0.085g of carbon quantum dots were added to 17g of deionized water, and stirred for 3h at a temperature of 35°C and a stirrer speed of 400r / min to obtain a carbon quantum dot dispersion with a concentration of 0.005g / mL; 0.4g of water chestnut starch (particle size ≤50μm) was added to 4g of deionized water, and then ultrasonically dispersed for 10min at an ultrasonic power of 300W and an ultrasonic frequency of 20kHz to obtain a water chestnut starch solution with a mass fraction of 9%;

[0060] 2) mixing the polyvinyl alcohol solution, the sodium carboxymethyl cellulose solution, the carbon quantum dot dispersion and the water chestnut starch solution, stirring for 2 h at a temperature of 25 ° C and a stirrer speed of 400 r / min, then heating to 85 ° C and stirring at a constant temperature for 10 min to obtain a gelatinized mixed slurry;

[0061] 3) The gelatinized mixed slurry was cast into a film, and then placed in a constant temperature and humidity chamber at a temperature of 30°C and a relative humidity of 40% for 60 hours to obtain a UV blocking film (surface density of 14.30 g / m 2 ).

[0062] Embodiment 4:

[0063] A UV blocking film, the preparation method of which is as follows:

[0064] 1) Add 0.2 g of polyvinyl alcohol (number average molecular weight of 250,000) to 4.8 g of deionized water, stir for 3 h at 90 ° C and 700 r / min to obtain a polyvinyl alcohol solution with a mass fraction of 4%; add 0.25 g of sodium carboxymethyl cellulose to 4.75 g of deionized water, stir for 2 h at 35 ° C and 350 r / min to obtain sodium carboxymethyl cellulose with a mass fraction of 5% Solution; add 0.1g of carbon quantum dots to 10g of deionized water, stir for 2h at a temperature of 35°C and a stirrer speed of 350r / min to obtain a carbon quantum dot dispersion with a concentration of 0.01g / mL; add 0.45g of water chestnut starch (particle size ≤50μm) to 4.5g of deionized water, and then ultrasonically disperse for 10min at an ultrasonic power of 300W and an ultrasonic frequency of 20kHz to obtain a water chestnut starch solution with a mass fraction of 9%;

[0065] 2) mixing the polyvinyl alcohol solution, the sodium carboxymethyl cellulose solution, the carbon quantum dot dispersion and the water chestnut starch solution, stirring for 2 h at a temperature of 25 ° C and a stirrer speed of 400 r / min, then heating to 85 ° C and stirring at a constant temperature for 10 min to obtain a gelatinized mixed slurry;

[0066] 3) The gelatinized mixed slurry was cast into a film, and then placed in a constant temperature and humidity chamber at a temperature of 30°C and a relative humidity of 40% for 72 hours to obtain a UV blocking film (surface density of 16.90 g / m 2 ).

[0067] Comparative Example 1:

[0068] A film, the preparation method of which is as follows:

[0069] 1) Add 0.3 g of polyvinyl alcohol (number average molecular weight of 300,000) to 4.7 g of deionized water, stir for 3 h at 90° C. and 700 r / min to obtain a polyvinyl alcohol solution with a mass fraction of 6%; add 0.3 g of sodium carboxymethyl cellulose to 4.7 g of deionized water, stir for 2 h at 35° C. and 450 r / min to obtain a sodium carboxymethyl cellulose solution with a mass fraction of 6%; add 0.4 g of water chestnut starch (particle size ≤ 50 μm) to 4 g of deionized water, and then ultrasonically disperse for 10 min at an ultrasonic power of 300 W and an ultrasonic frequency of 20 kHz to obtain a water chestnut starch solution with a mass fraction of 9%;

[0070] 2) mixing the polyvinyl alcohol solution, the sodium carboxymethyl cellulose solution and the water chestnut starch solution, stirring for 2 h at a temperature of 25 ° C and a stirring speed of 400 r / min, then heating to 85 ° C and stirring at a constant temperature for 10 min to obtain a gelatinized mixed slurry;

[0071] 3) The gelatinized mixed slurry was cast into a film, and then placed in a constant temperature and humidity chamber at a temperature of 30°C and a relative humidity of 40% for 72 hours to obtain a film (surface density of 12.74 g / m 2 ).

[0072] Comparative Example 2:

[0073] A film, the preparation method of which is as follows:

[0074] 1) Add 0.4 g of polyvinyl alcohol (number average molecular weight of 300,000) to 4.6 g of deionized water, stir for 4 h at a temperature of 90 ° C and a stirrer speed of 700 r / min to obtain a polyvinyl alcohol solution with a mass fraction of 8%; add 0.3 g of sodium carboxymethyl cellulose to 4.7 g of deionized water, stir for 3 h at a temperature of 35 ° C and a stirrer speed of 450 r / min to obtain a sodium carboxymethyl cellulose solution with a mass fraction of 6%; add 0.1 g of carbon quantum dots to 20 g of deionized water, stir for 3 h at a temperature of 35 ° C and a stirrer speed of 300 r / min to obtain a carbon quantum dot dispersion with a concentration of 0.005 g / mL;

[0075] 2) mixing the polyvinyl alcohol solution, the sodium carboxymethyl cellulose solution and the carbon quantum dot dispersion, stirring for 2 h at a temperature of 25° C. and a stirring speed of 400 r / min to obtain a mixed slurry;

[0076] 3) The mixed slurry was cast into a film, and then placed in a constant temperature and humidity chamber at a temperature of 30°C and a relative humidity of 40% for 48 hours to obtain a film (surface density of 10.40 g / m 2 ).

[0077] Performance Test:

[0078] 1) The ultraviolet blocking films in Examples 1 to 4 and the films in Comparative Examples 1 to 2 were cut into strips with a length of 5 cm and a width of 1 cm. After the thickness was measured, the mechanical properties were tested using an Instron 5967 universal testing machine (Instron Co., Ltd., USA) at a tensile speed of 1.25 mm / min. The test results are shown in the following table:

[0079] Table 1 Mechanical properties test results of the ultraviolet blocking films in Examples 1 to 4 and the films in Comparative Examples 1 to 2

[0080] Test items Sample thickness (μm) Tensile strength(MPa) Elongation at break (%) Example 1 37.21 138.26 4.82 Example 2 41.52 146.34 5.57 Example 3 38.33 154.11 6.75 Example 4 46.41 149.79 6.02 Comparative Example 1 42.50 129.21 4.12 Comparative Example 2 40.76 132.37 4.32

[0081] It can be seen from Table 1 that the tensile strength of the ultraviolet blocking films in Examples 1 to 4 is improved compared with the films in Comparative Examples 1 to 2, and as the carbon quantum dot content increases, the tensile strength of the film first increases and then decreases. When the weight percentage of carbon quantum dots reaches 8.5% (Example 3), the tensile strength of the film reaches a maximum value.

[0082] 2) The appearance of the ultraviolet blocking films in Examples 1 to 4 and the film in Comparative Example 1 is as follows: Figure 1 (The film sample is placed on a white paper with the word "Transparency" printed on it), the appearance of the film in Comparative Example 2 is shown in FIG. Figure 2 (The film sample is placed on a white paper with the word "Transparency" printed on it).

[0083] Depend on Figure 1 and Figure 2 It can be seen that the ultraviolet blocking films in Examples 1 to 4 and the films in Comparative Examples 1 to 2 have high transparency and good light transmittance.

[0084] 3) The UV-1900 UV-visible spectrophotometer was used to test the UV-blocking properties of the UV-blocking films in Examples 1 to 4 and the film in Comparative Example 1. The test results are as follows: Figure 3 shown.

[0085] Depend on Figure 3 It can be seen that compared with the film in comparative example 1, the transmittance of light in the ultraviolet region UV-A (315nm~400nm) and UV-B (280nm~315nm) bands of the ultraviolet blocking films in Examples 1 to 4 is significantly reduced, indicating that they have excellent ultraviolet blocking performance; as the content of carbon quantum dots in the ultraviolet blocking films in Examples 1 to 4 increases, the ultraviolet blocking performance of the films becomes more and more excellent.

[0086] 4) The water vapor transmission rate (WVTR) test results of the UV blocking films in Examples 1 to 4 and the film in Comparative Example 2 are as follows: Figure 4 As shown, the test results of moisture content (MC) and water solubility (WS) are as follows Figure 5 shown.

[0087] The test method of water vapor transmission rate (WVTR) is as follows: a centrifuge tube containing 30 mL of deionized water is sealed with a film sample, and then placed in a desiccator containing color-changing silica gel, placed at 25°C for 24 hours, and then the WVTR (in g / m 2 ·s): WVTR = ΔW / (T×A), where ΔW is the weight loss of deionized water (in g), T is the storage time (in s), and A is the exposed area of ​​the film (in m 2 ).

[0088] The test method for moisture content (MC) and water solubility (WS) is as follows: cut the film sample into 50mm×50mm sheets, weigh it, record it as M1 (in g), then dry it at 105°C to constant weight, weigh it, record it as M2 (in g), then place the dried film sample in a beaker containing 100mL of deionized water, seal it, soak it at room temperature for 24h, then take it out, and then dry it at 105°C to constant weight, weigh it, record it as M3 (in g), and then calculate MC and WS according to the following formula: MC(%)=(M1-M2) / M1×100%; WS(%)=(M2-M3) / M2×100%.

[0089] Depend on Figure 4 and Figure 5 It can be seen that the UV blocking films in Examples 1 to 4 have lower water vapor permeability than the film in Comparative Example 2, and as the content of horseshoe starch increases, the water vapor permeability of the UV blocking films in Examples 1 to 4 shows a slowly decreasing trend, while the moisture content and water solubility show an increasing trend. In particular, the moisture content of the UV blocking film in Example 4 reaches about 30%, indicating that the film in Comparative Example 2 has relatively poor moisture barrier performance, while the UV blocking films in Examples 1 to 4 are added with horseshoe starch with unique water absorption function, which can absorb moisture from the surrounding environment and reduce water permeability, thereby increasing the water barrier effect of the film and effectively improving the water absorption and barrier performance of the film.

[0090] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A UV blocking film, characterized in that: Made from the following raw materials in weight percentage: Polyvinyl alcohol: 20% to 40%; Sodium carboxymethyl cellulose: 20%-30%; Carbon quantum dots: 5% to 10%; Horse hoof starch: 30%~45%.

2. The ultraviolet light blocking film according to claim 1, characterized in that: The number average molecular weight of the polyvinyl alcohol is 250,000 to 300,000.

3. The ultraviolet light blocking film according to claim 1, characterized in that: The particle size of the carbon quantum dots is 5nm to 10nm.

4. The ultraviolet blocking film according to any one of claims 1 to 3, characterized in that: The particle size of the water chestnut starch is ≤50 μm.

5. The ultraviolet blocking film according to any one of claims 1 to 3, characterized in that: The surface density of the UV blocking film is 13 g / m 2 ~20g / m 2 .

6. A method for preparing the ultraviolet blocking film according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) adding water to dissolve / disperse polyvinyl alcohol, sodium carboxymethyl cellulose, carbon quantum dots and water chestnut starch respectively to prepare polyvinyl alcohol solution, sodium carboxymethyl cellulose solution, carbon quantum dot dispersion and water chestnut starch solution; 2) mixing the polyvinyl alcohol solution, the sodium carboxymethyl cellulose solution, the carbon quantum dot dispersion and the water chestnut starch solution uniformly, and then heating to perform gelatinization reaction to obtain a gelatinized mixed slurry; 3) Casting the gelatinized mixed slurry into a film, and then drying it to obtain a UV blocking film.

7. The preparation method according to claim 6, characterized in that: The mass fraction of the polyvinyl alcohol solution in step 1) is 4% to 8%; the mass fraction of the sodium carboxymethyl cellulose solution in step 1) is 5% to 6%; the concentration of the carbon quantum dot dispersion in step 1) is 0.005g / mL to 0.01g / mL; the mass fraction of the horseshoe starch solution in step 1) is 8% to 10%.

8. The preparation method according to claim 6 or 7, characterized in that: Step 2) The gelatinization reaction is carried out at a temperature of 80°C to 85°C, and the reaction time is 10min to 15min.

9. The preparation method according to claim 6 or 7, characterized in that: Step 3) The drying is carried out at a temperature of 30° C. to 40° C. and a relative humidity of 35% to 45%, and the drying time is 48 h to 72 h.

10. A food packaging material, characterized in that: The invention comprises the ultraviolet shielding film according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • High-efficiency oxygen-insulation water-insulation blended full-degradable plastic film and preparation method thereof

    CN104910434A

  • High-conductivity degradable plastic film composite material containing carbon nanotubes and preparation method of composite material

    CN106751332A

  • Carbon quantum dot-polyvinyl alcohol film and preparation method and application thereof

    CN108517097A

  • Macromolecule thin film material and method for preparing same

    CN108530690A

  • Polyvinyl alcoholic film

    JP1999029680A

Cited By

  • Preparation method of carbon quantum dot-polyvinylpyrrolidone-starch composite film and application of carbon quantum dot-polyvinylpyrrolidone-starch composite film in food fresh-keeping storage

    CN119798795A

  • Production method of high-strength waterproof polyvinyl alcohol film

    CN121930603A

  • A method for producing a high-strength water-resistant polyvinyl alcohol film

    CN121930603B